Functional outcome of microscopic lumbar discectomy for the treatment of lumbar disc prolapse - Abdul Aziz, Ansari Ishtyaque; Abdul Aziz, Ansari Muqtadeer (International Journal of Research in Orthopaedics, 2018)
Background: Back pain constitutes significant proportion of orthopaedic practitioner OPD. Lumbar disc prolapse constitutes important cause of back pain with radiculopathic leg pain. Different techniques have evolved to treat this disorder non-operatively and operatively. Operative techniques vary a lot in the field of spine surgery depending on the surgeon, institute, infrastructure and cost. We present simple, cost effective, cosmetic, operative technique with scientific basis which gives better visualization for decompression of nerve root in this paper called microscopic lumbar discectomy (MLD). Methods: On the basis of inclusion and exclusion criteria 26 patients were operated by microscopic lumbar discectomy (MLD) technique. All the patients were followed up at the interval of 1 month, 3 months and 6 months and assessment was done of subjective and objective findings with Japanese orthopaedic association (JOA) score and rate of improvement (RI) was calculated. Out of 26 patients 18 were men and 8 were women. Age ranges from 28 years to 72 years. Mean age being 47.8 years. Results: Out of 26 patients at the time of discharge, 20 patients (87.5%) could walk independently without any aid and without any radicular pain. In most of the patients 19 (73.07%) sciatica improved immediately. The pre-operative mean±SD (SE) JOA score was 8.346±0.85 (0.169) which improved to 11.807±0.694 (0.136) after 1 month and 13.19±0.895 (0.175) after 6 months. Conclusions: Excellent to good results and improvement can be achieved surgically, economically and cosmetically by microscopic lumbar discectomy technique in the spine lumbar disc prolapse patients at many spine centre with cosmesis, good results and rehabilitation of the patient.